Weight bias reduction in health professionals: a systematic review. Issue 3 (June 2016) - Alberga, A. S.; Pickering, B. J.; Alix Hayden, K.; Ball, G. D. C.; Edwards, A.; Jelinski, S.; Nutter, S.; Oddie, S.; Sharma, A. M.; Russell‐Mayhew, S.
Summary: Innovative and coordinated strategies to address weight bias among health professionals are urgently needed. We conducted a systematic literature review of empirical peer‐reviewed published studies to assess the impact of interventions designed to reduce weight bias in students or professionals in a health‐related field. Combination sets of keywords based on three themes (1: weight bias/stigma; 2: obesity/overweight; 3: health professional) were searched within nine databases. Our search yielded 1447 individual records, of which 17 intervention studies satisfied the inclusion criteria. Most studies ( n = 15) included medical, dietetic, health promotion, psychology and kinesiology students, while the minority included practicing health professionals ( n = 2). Studies utilized various bias‐reduction strategies. Many studies had methodological weaknesses, including short assessment periods, lack of randomization, lack of control group and small sample sizes. Although many studies reported changes in health professionals' beliefs and knowledge about obesity aetiology, evidence of effectiveness is poor, and long‐term effects of intervention strategies on weight bias reduction remain unknown. The findings highlight the lack of experimental research to reduce weight bias among health professionals. Although changes in practice will likely require multiple strategies in various sectors, well‐designed trials are needed to test the impact of interventions to decrease weight bias in healthcare settings.